Development of E-Physics Magazine Media with the Assistance of Canva to Increase Students' Interest in Learning Physics: A Feasibility Test - Haafida, Nuuri; Nur Diyana, Tsania (Prodi Fisika FKIP Unram, 2023)
Learning media is a tool that can assist teachers in conveying information to students so that the material can be conveyed thoroughly. Physics, which is seen as a difficult subject, requires alternative attractive media such as magazines in order to increase interest in reading and learning. The purpose of this research is to determine the feasibility of E-physics Magazine as an alternative physics learning media. The R&D research method is used with the 4D model which is carried out until the development stage. Feasibility test with 3 indicators was conducted by 1 lecturer and 6 active Physics Education students. The results of the feasibility test obtained are the material indicator getting an average result of 3.43, the media presentation indicator getting an average result of 3.08, and the language indicator getting an average of 3.46. So, it can be stated that E-physics Magazine is feasible to use as an alternative physics learning media. Keywords: E-physics Magazine, Ohm's Law, reading interest, learning interest